2020
DOI: 10.1002/edm2.216
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid involvement in threatened preterm labour

Abstract: Introduction The neurosteroid allopregnanolone modulates oxytocin expression in the brain, and its effects arise from its action on the GABAA receptor. Whether neurosteroid levels and the function of the GABAA receptor are involved in the risk of preterm labour in pregnant women is unknown. Methods Pregnant women with (n = 16) or without (n = 20) threatened preterm labour (TPL) in gestational week 33 + 6 days to 37 + 0 days were studied prospectively with procedures including foetal heart rate monitoring, vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(114 reference statements)
1
0
0
Order By: Relevance
“…Additionally, ALLO restrains maternal pituitary oxytocin production in late pregnancy, potentially delaying the onset of regular uterine contractions ( 20 ). Our results are consistent with a recent study that found no difference in maternal serum ALLO concentrations late in pregnancy between women with or without possible preterm labor ( 32 ). However, that work relied on quantification of a single blood sample at the time of hospital admission for preterm labor evaluation without considering preterm birth outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, ALLO restrains maternal pituitary oxytocin production in late pregnancy, potentially delaying the onset of regular uterine contractions ( 20 ). Our results are consistent with a recent study that found no difference in maternal serum ALLO concentrations late in pregnancy between women with or without possible preterm labor ( 32 ). However, that work relied on quantification of a single blood sample at the time of hospital admission for preterm labor evaluation without considering preterm birth outcomes.…”
Section: Discussionsupporting
confidence: 93%